Predicting Student Depression With Measures of General and Academic Anxieties - Cassady, Jerrell C.; Pierson, Eric E.; Starling, J. Michael (Frontiers in Education, 2019)
Universities are increasingly cognizant of the importance of attending to the psychological and emotional needs of undergraduate learners, recognizing that anxiety and depression have significant negative impacts on student retention and success. The focus of the current study was to evaluate the connections among various forms of anxiety and examine the relationships these indicators of anxiety have with depression. The results demonstrated that a broad measure of neuroticism was a meaningful predictor for depression. However, precision in detecting depressive symptoms was improved when examining an additional measure specifically focused on academic anxiety. The results provide support for a nested model of anxiety, which suggests that broad neuroticism, then academic anxiety, and finally test anxiety are progressively more specific manifestations of anxious indicators in university students.